On chronicle and recent exploit of a special clone of free energy (hyper) beneficial to thermodynamic description of partially open geological, metallurgical and other nonstoichiometric systems - Šesták J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Founding and determination of thermodynamic functions related to solid often geologic materials is traced showing interactions between Czech Professor F. Wald and Russian R.S. Kurnakov and D.S. Korzhinskiĭ in the early definition of phases and characterization of partly open systems. Development of thermodynamic notions regarding solid-state-gas description by P. Holba is reviewed showing its consequence in geology and metallurgy. For the joint definition of operate of mobile components the hyper-free energy was developed and recently put into function in nonstoichmetric systems. Novel even if unusual term of the associated new variable plutability is explained. Instigators of modern thermodynamic educate in both the Czechia and Serbia is made more noticeable.